Persistent Asthma and the Role of Contextual Care in Family Medicine Practice - Mir A. Dzikro; Rifda El Mahroos; Prasetyaning E. Pratiwi (Medical Scope Journal, 2026)
Abstract: Asthma is a chronic inflammatory airway disease with symptoms influenced by biological, environmental, and psychosocial factors. We reported a 48-year-old woman with persistent uncontrolled asthma presenting with daily and nocturnal symptoms, activity limitation, and recurrent exacerbations. Spirometry demonstrated severe obstructive impairment with mild restriction (FEV₁ 30%, FEV₁/FVC 35%), indicating advanced disease progression. The patient was managed holistically through pharmacological therapy following the Global Initiative for Asthma (GINA) 2024 guidelines and non-pharmacological strategies including education, lifestyle changes, stress control, family support, and environmental modification. After implementing family medicine interventions, the patient demonstrated improved symptom control, reduced nocturnal asthma attacks, better treatment adherence, improved sleep quality, and increased awareness regarding trigger avoidance and environmental hygiene. In conclusion, this case emphasizes the importance of contextualized family medicine in asthma care. Keywords: asthma; family medicine; holistic health; primary care; chronic inflammatory disease